(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
Uzbek national education system. In particular, it changed the purpose of literary education - now the main goal is to bring up children on the basis of virtues, educated, highly competent, loyal to the motherland and the people, physically healthy, deep and independent thinker.